Kryzys społeczeństwa kapitalistycznego a (nowa) kwestia miejska - Baranowski, Mariusz (Kultura i Społeczeństwo, 2016)
This article addresses the problem of the crisis of capitalist society, as described by Alain Touraine, through the example of urban space. It attempts to trace the symptoms of the crisis in the context of the urban question, understood as the set of (potential or actual) dysfunctional consequences of the organization of social life in accord with individual and/or collective expectations within the sphere of the city.